Spring viremia of carp - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2024)
SVC infections have been reported in a number of cyprinid fish species such as common carp, koi carp. Four strains of SVC have been reported include genogroup Ia, Ib, Ic and Id. Vector transmission could be occurred via carp louse (Argulus foliceus), leech (Piscicola geometra). Clinical signs revealed exopthalamos, petechial hemorrhage at skin, base of fin and cloaca. Histhopathological alteration showed oedematous perivasculitis and necotized hepatic tissue, hyperaemia and proliferation of reticuloendothelium and melanomacrophage centre in splenic tissue and pericarditis concurrent with myocardial degeneration. Detection of viral antigen, nucleic acid, virus isolation and identification was recommended for confirmatory diagnostic method. SVC disease control methods focused on avoiding exposure to the virus through farm hygienic practices, water treatment before fish cultivation.